Geographical Information System of Disaster Victims Location Using Web-Based and Mobile Application - Puji Winar Cahyo; Naufal Asyhab; Ahmad Subhan Yazid; Muhammad Taufiq Nuruzzaman (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2014)
Disasters that have occurred in the city of Yogyakarta, causing no casualties were relatively few. Result of the many victims of the disaster led to the spread of location affected to some areas. Then it takes the system is fast in the submission of data in each affected area. Method of UML (Unified Modeling Language) is used to build this system, the method UML is focused in the development of object-oriented systems, suitable for use in android programming, CodeIgniter PHP framework that accommodates the library Google Map. Mobile apps (android) is used as a client that handles input data disaster victims, Geographic Information Systems (GIS) as a server whose job is to receive and data mapping disaster victims. Coordinator unit rescue can send disaster relief information notice to each member through a GIS that has been communicated to the SMS Gateway (Short Message Service). Geographic Information System of Disaster Victims Location Using Web-Based and Mobile Application built to help control aid disaster victims, especially accuracy in mapping location of the disaster victims, because it uses a GPS (Global Positioning System) to determine the coordinates of disaster victims.